Enfoques y metodologías de las ciencias sociales : una perspectiva pluralista - Della Porta, Donatella, 1956-; Keating, Michael, 1950-; Vázquez Ramil, Raquel (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2013)
This volume will empower students to choose their own approach to research in the social sciences, to justify this approach, & to situate it within the discipline. It addresses questions of ontology, epistemology & philosophy of social science, as well as issues of methodology & research design essential for a good research proposal.
Introducción / Donatella della Porta y Michael Keating -- ¿Cuátos enfoques hay en ciencia sociales? : introducción epistemológica / Donatella della Porta y Michael Keating -- Teoría política normativa e investigación empírica / Rainer Bauböck -- Explicación causal / Adrienne Héritier -- Constructivismo : qué (no) es y su importancia / Friedrich Kratochwil -- Culturea y ciencia social / Michael Keating -- Institutionalismo histórico / Sven Steinmo -- Teoría de los juegos / Christine Chwaszcza -- Racionalidad y reconocimiento / Alessandro Pizzorno -- Conceptos y formación de conceptos / Peter Mair -- Análisis comparativo : la investigación basada en casos frente a la investigación basada en variables / Donatella della Porta -- Estudios de caso y seguimiento de procesos : teorías y prácticas / Pascal Vennesson -- Análisis cuantitativo / Mark Franklin -- El diseño de la investigación social y política / Philippe Schmitter -- Enfoques etnográficos / Zoe Bray -- Comparación entre enfoques, metodologías y métodos. Conclusiones finales / Donatella della Porta y Michael Keating.
Online resource; title from PDF title page (Digitalia, viewed October 24, 2014)
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Electronic books